Xuebijing injection inhibited neutrophil extracellular traps to reverse lung injury in sepsis mice via reducing Gasdermin D - Shang, Ting; Zhang, Zhi-Sen; Wang, Xin-Tong; Chang, Jing; Zhou, Meng-En; Lyu, Ming; He, Shuang; Yang, Jian; Chang, Yan-Xu; Wang, Yuefei; Li, Ming-Chun; Gao, Xiumei; et al. (Frontiers in Pharmacology, 2022)
The mortality of sepsis and septic shock remains high worldwide. Neutrophil extracellular traps (NETs) release is a major cause of organ failure and mortality in sepsis. Targeting Gasdermin D (GSDMD) can restrain NETs formation, which is promising for sepsis management. However, no medicine is identified without severe safety concerns for this purpose. Xuebijing injection (XBJ) has been demonstrated to alleviate the clinical symptoms of COVID-19 and sepsis patients, but there are not enough animal studies to reveal its mechanisms in depth. Therefore, we wondered whether XBJ relieved pulmonary damage in sepsis by suppressing NETs formation and adopted a clinically relevant polymicrobial infection model to test this hypothesis. Firstly, XBJ effectively reversed lung injury caused by sepsis and restrained neutrophils recruitment to lung by down-regulating proinflammatory chemokines, such as CSF-3, CXCL-2, and CXCR-2. Strikingly, we found that XBJ significantly reduced the expressions of NETs component proteins, including citrullinated histone H3 (CitH3), myeloperoxidase (MPO), and neutrophil elastase (NE). GSDMD contributes to the production of NETs in sepsis. Notably, XBJ exhibited a reduced effect on the expressions of GSDMD and its upstream regulators. Besides, we also revealed that XBJ reversed NETs formation by inhibiting the expressions of GSDMD-related genes. Collectively, we demonstrated XBJ protected against sepsis-induced lung injury by reversing GSDMD-related pathway to inhibit NETs formation.